Recovery is no laughing matter – or is it? - Barker, Alex Byron; Winship, Gary (Emerald, 2016)
Purpose - The purpose of this paper is to describe an exploratory pilot study to assess the methods used to evaluate an innovative programme of comedy workshops for a small cohort of people recovering from substance misuse problems. The comedy workshops involved participants working with a professional comedian-to explore, develop, write and finally perform a stand-up comedy routine drawing from their own personal experiences. Design/methodology/approach - The impact of the programme was gauged using questionnaires; the Warwick-Edinburgh Mental Well-being Scale, the Rosenberg Self-Esteem Scale, the General Self-Efficacy, Scale and the Life Orientation Test-Revised and Eco-Mapping Tool. Findings - Ten participants began the programme with four participants following through to public performance at an evening showcase event. The quantitative measures showed favourable results on three positive outcome measures; psychological well-being, self-esteem and self-efficacy. Participant's number of social relationships and strength of relationships decreased following the intervention, however, relationships were more mutual and were characterized by less conflict following the workshop. Research limitations/implications - The small sample limits generalization of this study, but the methods for data collection were found to be feasible. Preliminary findings suggest that the workshops have a positive impact on recovery. Originality/value - This paper describes an evaluation of an innovative programme of comedy workshops for people recovering from substance abuse problems. The preliminary findings point to a new hypothesis about recovery, that successful recovery might be characterized by a smaller social network, with stronger mutual bonds.